Perilaku Pedagang Kaki Lima Dalam Perspektif Etika Bisnis Islam Di Kawasan Taman Kota Selong: The Behavior of Street Vendors in the Perspective of Islamic Business Ethics in the Selong City Park Area - Siti Shofia Wardani; Busaini Busaini (LPPM Institut Studi Islam Sunan Doe, 2022)
Business ethics is a manifestation of the ethical principles of business conduct, which must be well understood so that people can get the greatest benefit from the buying and selling activities carried out. The purpose of this research is to find out whether the behavior of street vendors is in accordance with Islamic business ethics. This type of research is field research (field research) using qualitative methods which are carried out descriptively. This study uses a qualitative method, because it examines reality, phenomena or symptoms that are holistic/intact, complex, dynamic and full of meaning. Data collection techniques were carried out by means of observation, interviews, recordings and photographs. Informants were determined while in the field using the snowball sampling technique. Based on the results of the study stated: the understanding of street vendors in the Taman Kota Selong area regarding Islamic business ethics, it can be concluded that traders do not know Islamic business ethics, however, in carrying out their trading activities they have applied rules that are justified in Islamic religious teachings: the principle of balance , the principle of the Will to do something (ikhtiyār), the principle of accountability (farḍ), and Virtue (Ihsan).